Stabilization of a class of $ψ$-Caputo fractional homogeneous polynomial systems - Omri, Faouzi (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.9In a constructive way, we study the problem of stabilization of $ψ$-Caputo fractional homogeneous polynomial systems. By using the Lyapunov functions, we construct stabilizing feedback laws for the analyzed fractional system. A numerical example is given to illustrate the efficiency of the obtained result.